Die Transparenz öffentlich-rechtlicher Rundfunkanstalten - Schmitt, Friedrich (Materialien zur rechtswissenschaftlichen Medien- und Informationsforschung, 2023)
Since the adoption of the broadcast license fee, transparency of public service media has been a topic of sociopolitical relevance in Germany. With this in mind, this study examines both the legal disclosure requirements applying to public service media concerning, among others, the compensation of leading personnel, as well as the individual right of access to information from public broadcasting corporations. The study concludes that transparency of public service media is, above all, subject to the prerogative of the legislation by the federal states, but that the German basic law demands transparency in some areas and allows it in others.